Cidadania vis-a-vis democracia : estudo analitico-interpretativo das greves, nos anos 80, como fenomeno indicador de mudanças nas relações do trabalho em instituições universitarias da administração publica federal : UFRJ e UFF - Costa, Maria Lygia Silva Magalhães (1992)
Strikes during the eighties at the Federal University of Rio de Janeiro (UFRJ) and Fluminense Federal University (UFF) are studied as an indicator of changing labor relations in Brazilian federal universities. The core research is based on increasing rniddle-class trade unionism in the public sector during the eighties. It is developed in order both to understand and to interpret the new union action paradigm that points out changes in the socio-political role of individual and collective actors vis-a-vis the practice of associative issues in federal universities. The methodology chosen is a qualitative approach to the subject, using as categories of analysis: citizenship, democracy, participation and power. They were used for comparing the strike movements at UFRJ and UFF. The study concludes that faculty as well as technical and management staff at both universities assumed. through organized participation in strike movements, new social roles and political positions, building a new concept of citizenship and, consequently, yielding changes in labor relations between public sector professional categories and the federal government. Due to their influence and associative lifestyle, these categories became socio-political forces with power to rnodify political and administrative decisions related to public policy formulation and management, specially those involving federal universities (IFES) personnel, benefits and salaries, as well as third leveI education funding.